Comparison of rainfall and water requirement for rice during rice growing period in Kirtipur, Nepal - Aryal, S. (Nepal Journal of Environmental Science, 2013)
An experiment was conducted to estimate the crop water requirement of rice and to compare it with the amount of rainfall. Experiment was designed to estimate evaporation and evapotranspiration in cylindrical half cut mineral water bottles. Rice was planted in the bottles to estimate evapotranspiration. The amount of rainfall during the experiment period was recorded in the rain gauge station. The evaporation was highest in the month of September (3.16 mm/day) and lowest in June (2.56 mm/day). The rate of evapotranspiration was in increasing order from June to September ranging from 3.43 mm/day in June to 19.57 mm/day for September. The crop water requirement was in increasing order reflecting more water demand with the increase in days after plantation and successive developmental stage of rice. The total amount of rainfall in the study area over study period (23rd June to 30th September, 2005) was 549.59 mm. The total crop water requirement of rice for same period in the same area was 711.45 mm. It showed that the rainfall during the study period was insufficient to meet the water demand for rice in the study area.